Obispo, financista y político: el doctor don Feliciano de Vega y Padilla (1580-1641) - Gálvez Peña, Carlos M. (Pontificia Universidad Católica del Perú. Fondo Editorial, 2012)
Don Feliciano de Vega y Padilla (1580-1641) was one of the most distinguished members of the Peruvian colonial episcopate in the first half of the seventeenth century, and the only one who, after an outstanding ecclesiastical career, was appointed archbishop of Mexico. His passionate life, professional profile and intellectual production make Don Feliciano an interesting case study in order to understand the complex and tense dynamics of power linking Royal Patronage and the most important religious and political institutions in the city of Lima during the early colonial period. The study of Dr. Vega’s life and work also shedslight on the first generation of colonial intellectuals who debated the rights of Creole subjects. The works written by Bishop Vega constitute some of the first written expressions of the defense of prelacies and offices within the colonial Church, and the debate over the doctrine of Distributive Justice which was used to justify these claims. This article analyzes the relationship between Bishop Vega and the principal viceregal institutions: the university, the archbishopric, the cathedral chapter and the Royal Audience. Finally, it will analyze how Lima’s elite citizens, of which Vega was one, manipulated these institutions.

Don Feliciano de Vega y Padilla (1580-1641) fue acaso la personalidad más destacada y emblemática del episcopado virreinal peruano de la primera mitad del siglo XVII. Luego de una brillante carrera en la universidad y el cabildo catedralicio de la ciudad de Lima, llegó a presidir tres diócesis hispanoamericanas, siendo la última de ellas el arzobispado de México. Su perfil profesional yproducción intelectual lo convierten en una de las figuras más influyentes de la elite social limeña y de la burocracia religiosa imperial de su tiempo. Su vida y su obra también ayudan a entender la trama de poder y la compleja dinámica de las relaciones entre la Corona y el virreinato peruano. Su poco conocida obra constituye una de las piedras angulares de la tradición memorialista peruana, interesada en la defensa de los derechos de prelación y el debate sobre la doctrina de la justicia distributiva. Este artículo analiza la conexión entre el doctor Vega y las principales instituciones virreinales: la universidad, el arzobispado, el cabildo catedralicio y la Real Audiencia. Asimismo, se estudia la manipulación de dichas instituciones por parte del grupo de los beneméritos, al que Vega perteneció.
Keywords: Historia; https://purl.org/pe-repo/ocde/ford#6.01.01